The error is in the second step they subtracted 3 from both sides but it was a 3x, which you can not do.
Correction.
9x+18+3x=1
12x+18=1
12x=-17
x=-17/12
<u><em>Answer: =-7.5+20y</em></u>
Step-by-step explanation:
distributive property: a(b+c)=ab+ac
a=-2.5, b=3, c=8y
-2.5*3-(-2.5)*8y
3(-2.5)-8(-2.5)y
simplify by equation.
3(-2.5)-8(-2.5)y=-7.5+20y
=-7.5+20y
Hope this helps!
Thanks!
Have a great day!
Answer:
60x + 25 + 60y
Step-by-step explanation:
60 times x plus 60 times y plus 25
16 blocks = 4 steps
x blocks = 50 steps
(16 blocks x 50 steps)/4 steps
= 200 blocks
Step-by-step explanation:
<u>Given</u>
- f(x) = 4x³ + 3x² - 2x - 1
<u>Divide it by the following:</u>
<u>(a) 2x + 1</u>
- 4x³ + 3x² - 2x - 1 =
- (4x³ + 2x²) + (x² + 1/2x) - (5/2x + 5/4) + 1/4 =
- 2x²(2x+1) + 1/2x(2x + 1) - 5/4(2x + 1) + 1/4 =
- (2x + 1)(2x² + 1/2x - 5/4) + 1/4
Quotient = 2x² + 1/2x - 5/4
Remainder = 1/4
<u>(b) 2x - 3</u>
- 4x³ + 3x² - 2x - 1 =
- (4x³ - 6x²) + (9x² - 13.5x) + (11.5x - 17.25) + 16.25 =
- (2x -3)(2x² + 4.5x + 5.75) + 16.25
Quotient = 2x² + 4.5x + 5.75
Remainder = 16.25
<u>(c) 4x - 1</u>
- 4x³ + 3x² - 2x - 1 =
- (4x³ - x²) + (4x² - x) - (2x - 1/2) - 3/2 =
- (4x - 1)(x² + x - 1/2) - 3/2
Quotient = x² + x - 1/2
Remainder = - 3/2
<u>(d) x + 2</u>
- 4x³ + 3x² - 2x - 1 =
- (4x³ + 8x²) - (5x² + 10x) + (8x + 16) - 17 =
- (x + 2)(4x² - 5x + 8) - 17
Quotient = 4x² - 5x + 8
Remainder = - 17